Experiment investigation on the influence of low pressure on ceiling temperature profile in aircraft cargo compartment fires. (5th October 2015) - Wang, Jie; Lu, Song; Guan, Yu; Lo, Siuming; Zhang, Heping
Abstract: The objective of the present study is to evaluate the low pressure effects on ceiling temperature profile in aircraft cargo compartment fires, which will affect the activation of fire detectors. A Series of fire tests were carried out in a full scale simulated aircraft cargo compartment at four atmospheric pressures (100 kPa, 90 kPa, 80 kPa and 70 kPa) corresponding to the pressure within an actual aircraft cargo compartment from the sea level to the cruising altitude (about 10, 000 m). Results show that the maximum ceiling temperature increases and the ceiling temperature decays faster as ambient pressure reduces. The air entrainment ratio C α is proposed in the correlation to predict the maximum ceiling temperature based on previous plume theory, considering the low pressure effect and entrainment coefficient. Meanwhile, modified by the air entrainment ratio C α, the previous classic correlations established by Alpert, Heskestad and Delichatsios for the ceiling temperature decay profile are further extended to low pressure conditions. The results based on Heskestad and Delichatsios method are more accurate than that of Alpert method in the experiments. All these findings would provide theoretical basis for the design of fire detection system in the aircraft cargo compartment. Highlights: Ceiling thermal characteristics of aircraft cargo compartment at various pressures. Air entrainment ratio has been proposed for the ceiling temperature correlations. Ceiling maximum temperature has been predicted for low pressure conditions. Ceiling temperature decay profile has been correlated for low pressure conditions.